Current Status and Policy Solutions to Promote the Integration of Science and Technology Activities with Training Activities at Universities in Vietnam - Xuan Huy, Nghiem; Thi Hoai, Tran; Vu Anh, Bui; Tien Nhat, Ngo; Xuan Du, Phung; Van Huy, Dao; Thai Ba, Nguyen; Van Tich, Vu; Loc, Nguyen; Thi Thanh Hai, Pham; Thi Thu Ha, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 38 No 1, 2022)
The article presents the results of research to assess the current situation of how science and technology activities and training activities have been integrated at Vietnamese universities in the context of the Industrial Revolution 4.0 (IR4.0). Aspects to be considered are: Perception of students, lecturers, managers about the impact of IR4.0 on learning and research activities; Model of scientific and technological activities (SRIC) at universities; The applying level of research results in training and teaching activities; and Policies and resources to ensure the connection between training and science and technology at universities. Survey data was conducted at 6 higher education institutions nationwide and with the obtained survey sample of 392 administrators, 1410 lecturers and 2311 students. The initial survey results show that the level of awareness about the impact of the industrial revolution 4.0 on the roles and professional activities of lecturers and students is not as high as expected; students' participation in scientific research activities in the learning process is not high; the coordination of universities with enterprises and research centers in training activities still has shortcomings; the link between research activities and training activities of each lecturer is still limited; and policies to encourage research, technology transfer and promote the integration of research and training have not been properly synchronized and effective. From the survey and analysis results, the paper proposes policy solutions to strengthen the integration of science and technology activities with training at universities, thereby improve the quality of research and training at research-oriented universities in Vietnam. Keywords Higher education; integration of training and research; scientific and technological activities; research-oriented university; research policy; education policy. References [1] M. Elken, S. Wollscheid, The Relationship Between Research and Education: Typologies and Indicators, Report 2016:8, Nordic Institute for Studies in Innovation, Research and Education (NIFU), 2016. [2] M. Robles, The Relationship Between Academic Research and Instructional Quality, Association for Business Communication Annual Conference Proceedings, 2016. [3] Callaghan & Coldwell, Research Versus Teaching Satisfaction and Research Productivity, International Journal of Educational Sciences, Vol. 7, No. 1, 2014, pp. 203-218. [4] J. Hattie, H. W. Marsh, The Relationship Between Research and Teaching: A Metaanalysis. Review of Educational Research, Vol. 66, No. 4, 1996, pp. 507-542. [5] M. A. Harkins, Leapfrog Principles and Practices: Core Components of Education 3.0 and 4.0, Futures Research Quarterly, Vol. 24, No. 1, 2008, pp. 19-31. [6] J. Wonglimpiyarat, The Innovation Incubator, University Business Incubator and Technology Transfer Strategy: The case of Thailand, Technology in Society, Vol. 46, 2016, pp. 18-27. [7] World Economic Forum, The Future of Jobs: Employment, Skills and Workforce Strategy for the Fourth Industrial Revolution, January, 2016. [8] World Economic Forum 2017, Preparing for Fourth Industrial Revolution Requires Deeper Commitments to Education, 2017. [9] P. U. Lijie, Innovation & Entrepreneurship Education at Nanjing University, Asian University Forum, Mogolia, Vol. 6, 2017. [10] D. Janssen, C. Tummel, A. Richert, and I. Isenhardt, Virtual Environments in Higher Education – Immersion as a Key Construct for Learning 4.0, iJAC, Kassel University, ISSN 1867-5565, Vol. 9, No. 2, 2016, [11] R. Brown, Mission Impossible? Entrepreneurial Universities and Peripheral Regional Innovation Systems. Industry and Innovation, Vol. 23, No. 2, 2016. [12] M. Stagars, University Startups and Spin- Offs: Guide for Entrepreneurs in Academia, Apress, 2015. [13] M. Healey, Linking Research and Teaching Exploring Disciplinary Spaces and the Role of Inquirybased Learning, Reshaping the University: New Relationships Between Research, Scholarship and Teaching, 2005, pp. 67-78.